Analysis of the use of Angular and Svelte products in mobile web applications - Nurzyński, Michał; Badurowicz, Marcin (Journal of Computer Sciences Institute, 2025)
The aim of this article is to analyze the use of Angular and Svelte tools in the development of a web application. The analysis focused on a custom application that allows measuring component rendering times and application build parameters. The research scenarios also considered the popularity of the frameworks. The results indicate higher performance for a small application created with Svelte, while Angular enjoys greater popularity.